A glimpse at women entrepreneurs in Penang - Zarina Md Nor; Zuraidah Ramli (Penerbit Universiti Kebangsaan Malaysia, 2016)
Women entrepreneurship is a force to be reckoned with. Women in business are commonly found all over the country and they help to create vibrant economic activities in domestic arena. This study focuses on the characteristics of 50 women entrepreneurs in the state of Penang, Malaysia. Among others, we find that many of them are stay-at-home married women with children. Therefore, they have to juggle and find balance between family life and their business. It is interesting to note that 84 percent come from families with entrepreneurial experiences. Therefore, it is fair to say that this kind of exposure has cultivated interest among these women to become entrepreneurs themselves. Further, family support has been one of the important factors that encourage these women to venture into businesses. However, despite their involvement in business, 50 percent of our respondents have not attended any training and courses on entrepreneurship. It seems that they rely more on advices from family members on issues related to their business compared to formal or government institutions. This is probably due to their reliance on personal savings and family sources of capital in embarking into the businesses such that institutional involvement is minimal in charting the direction of their businesses though they are aware of various kinds of financial assistance provided by the government. Hence, even in a smaller scale, women entrepreneurs are increasingly creating wealth for the nation while simultaneously caring for their families.